SOME CONSIDERATIONS ON THE ANALYSIS OF HISTORICAL HERITAGE - Ya.Kh. Gaffarov (The Bioscan, 2024)
This article analyzes that national values, their state, future fate are one of the problems that have always interested people. It was also shown that the memory of our national heroes who gave their lives for the Motherland and the freedom of the people, the activities of scientists who gave their lives for the nation, today's attitude to our historical heritage and culture have changed radically.